2015
DOI: 10.1016/j.anbehav.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Early life adversity increases foraging and information gathering in European starlings, Sturnus vulgaris

Abstract: Animals can insure themselves against the risk of starvation associated with unpredictable food availability by storing energy reserves or gathering information about alternative food sources. The former strategy carries costs in terms of mass-dependent predation risk, while the latter trades off against foraging for food; both trade-offs may be influenced by an individual's developmental history. Here, we consider a possible role of early developmental experience in inducing different mass regulation and fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 68 publications
4
26
1
Order By: Relevance
“…The developmental induction of high adult body weight by early-life adversity has been observed in many species, including humans4748495051, and our own previous work in starlings52. Our results here showed that induction of relatively high body in the juvenile starling requires not just early nutritional restriction, but the combination of early nutritional restriction and a low level of effort required to obtain food.…”
Section: Discussionsupporting
confidence: 73%
“…The developmental induction of high adult body weight by early-life adversity has been observed in many species, including humans4748495051, and our own previous work in starlings52. Our results here showed that induction of relatively high body in the juvenile starling requires not just early nutritional restriction, but the combination of early nutritional restriction and a low level of effort required to obtain food.…”
Section: Discussionsupporting
confidence: 73%
“…There was no evidence that either of our developmental treatments, nor their interaction, had any systematic effect on adult dominance as measured in competition over a food resource. Thus, our suggestion that the behavioural phenotype we have documented as a consequence of early adversity, involving reduced dietary selectivity (Bloxham et al., 2014) and hyperphagia (Andrews et al., 2015), is due to birds that experienced greater adversity being more subordinate as adults, does not appear to be supported in this cohort of birds. This conclusion remains unaltered if we use developmental telomere attrition as the measure of early adversity, rather than experimental group: developmental telomere attrition did not predict adult dominance in competition for food.…”
Section: Discussionmentioning
confidence: 99%
“…However, a widespread conclusion in developmental programming research is that small changes to the nature, timing, or severity of developmental treatments can produce different or even opposite effects on the adult phenotype (Love and Williams 2008; Kriengwatana et al 2014). In our own work, for example, we have observed different types of early-life adversity producing both lower and higher long-term adult body weights (Andrews et al 2015; Dunn et al 2018). Thus, it may be that our hand-rearing paradigm, rather than being a more controlled model of a brood-size manipulation in the wild, actually has qualitatively different effects.…”
Section: Discussionmentioning
confidence: 94%